Techno-economic optimization model for sustainable insulation material developed for energy efficiency - Balo, Figen; Sua, Lutfu S. (Wiley, 2018)
Renewable insulation materials are produced within the scope of this study using clay, fly ash, expanded perlite, epoxidized hemp oil, and hemp fiber. Density, thermal conductivity, and compressive-tensile strength of the produced materials are analyzed. Economic and environmental analysis of the best sample with the most appropriate characteristics for an insulation material is conducted using a hybrid mathematical model developed for this study. Mathematical formulas of an economic evaluation technique of P-1-P-2 method is integrated into Simulated Annealing Algorithm as one of the metaheuristic optimization approaches. Applicability of the proposed material for externally insulated walls is tested. For this purpose, optimum insulation thickness, payback period, energy savings for 10 years of lifetime, and CO2-SO2 emissions were calculated for 5 types of energy sources along with a sensitivity analysis. This method is developed and coded in a software platform and used for the first time for the optimization of insulation material thickness. The experimental results obtained from evaluation of the sample H36 indicate that using this material for insulation purposes in the buildings have the potential of making significant contribution for energy efficiency along with various environmental benefits.
Keywords: simulated annealing; green insulation material; hemp fiber; metaheuristic optimization; modified vegetable oil